Preliminary Estimation of the Transmission Risk of Novel Coronavirus in Hubei Province (Journal of Nonlinear Modeling and Analysis, 2025)
A novel coronavirus (COVID-19) causes an outbreak of viral pneumonia in Wuhan, Hubei province, China. In this paper, the deterministiccompartmental model is given based on the clinical progression of the diseaseand the intervention measures implemented by the Chinese authorities. Simulations of the model are given to estimate the basic reproduction numberfor COVID-19 based on the daily reported cases from China CDC. The basic reproduction number of the model is used to assess the transmissibility ofCOVID-19. The results indicate that COVID-19 will be controlled at the endof March if there are no imported infections people into China. Then the first-level public health emergency response can be adjusted to the second-level orthe higher-level response.
Keywords: COVID-19; the basic reproduction number; two-stage mathematical model.